Whose Line Is It? Plagiarism in Economics - Enders, Walter; Hoover, Gary A (Journal of Economic Literature, 2004)
This paper reports the results of a survey regarding the instances of plagiarism reported by journal editors in the economics profession. The survey finds that nearly 24% of responding editors encounter one case of plagiarism in a typical year. In addition, the survey reveals that less than 19% of responding journals have a formal policy regarding plagiarism. Moreover, there is a great deal of variance in what is considered plagiarism and what an appropriate response to plagiarism should be. A majority of editors believe that the economics profession would benefit from a professional code of ethics.